2022
DOI: 10.1002/ajoc.202100797
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Synthesis of Cyclohexanedione‐fused 2,8‐Oxaza/2,8‐Dioxa Bicyclo[3.3.1]nonanes and 4‐Substituted 4H‐Chromenes by Tunability of the Deamination/Dehydration Process

Abstract: In this study, a concise and efficient protocol for the construction of diverse cyclohexanedione-fused 2,8oxaza/2,8-dioxa bicyclo[3.3.1]nonanes and 4-substituted 4Hchromenes between 2-hydroxychalcones and 3-aminocyclohex-2-enones has been accomplished. This switchable syn-thesis concerning the three types of functionalized heterocyclics via tunability of the deamination/dehydration process was controlled by Brønsted acid catalyst or solvent effects in this cascade transformation, which can thus provide the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Very recently, Liu and Huang employed 3-aminocyclohex-2-enones as nucleophile, and accomplished cascade reactions for the divergent synthesis of polyheterocycles and 4-substituted 4H-chromenes. [40] The selective synthesis of each category was controlled by the solvent used. It was found that n PrOH turned out to be the right reaction medium for the generation of 4-substituted 4H-chromenes 169 from 2-hydroxychalcones 67 and 3-aminocyclohex-2-enone 168 under catalyst-free and reflux condition within 20 h (Scheme 42).…”
Section: Cyclization On the 2-hydroxychalcone Moietymentioning
confidence: 99%
“…Very recently, Liu and Huang employed 3-aminocyclohex-2-enones as nucleophile, and accomplished cascade reactions for the divergent synthesis of polyheterocycles and 4-substituted 4H-chromenes. [40] The selective synthesis of each category was controlled by the solvent used. It was found that n PrOH turned out to be the right reaction medium for the generation of 4-substituted 4H-chromenes 169 from 2-hydroxychalcones 67 and 3-aminocyclohex-2-enone 168 under catalyst-free and reflux condition within 20 h (Scheme 42).…”
Section: Cyclization On the 2-hydroxychalcone Moietymentioning
confidence: 99%
“…Another method of preparing this type of skeleton involves the annulation of the flavylium ion with phloroglucinol, which was discovered by Jurd et al in a biomimetic synthetic study in 1965 (Scheme A-ii) and further exploited by various other groups . Other than these, the rest of the methods mostly evolved around a similar precursor, i.e., 2-hydroxy chalcones, with different reaction partners (Scheme A-iii) . Therefore, developing new methodologies for constructing these diaryl-substituted 2,8-dioxabicyclo[3.3.1]­nonanes remains highly desirable.…”
Section: Introductionmentioning
confidence: 99%